Behavior of bolted beam-column joints under sudden column removal - See, Chee Han (2014)
Application of steel in the building industry is getting popular nowadays. Hence, robustness of connections and structures has been a very keen area of research by researchers around the world. Interest in the subject was further advocated by many disastrous events involving collapse of buildings, which happened to occur from time to time. Therefore, this dissertation is aiming to investigate the behavior of bolted beam connection in the event of a dynamic event such as progressive collapse under sudden column removal scenario. A Finite Element Model (FEM) of a fixed end plate connection was applied as the subject of analysis. In order to perform the analysis of FEM in a detailed way,Abaqus software was used. This is because the 3D model can display and portray all surface interactions as well as properties of material non-linearity. The analyses were performed by imposing different loads at both steel beams as tying forces on the connection. During the dynamic analysis at the same load instances, it was found that the connection model underwent further deformation than the static load case until the whole frame collapsed eventually. Several parametric studies are done to further investigate the effect of bolted beam column connection under a sudden column removal scenario.